Preparation method of battery-grade lithium zirconate

Through zirconia purification and wet mixing methods, the problems of high synthesis temperature and impurity in the preparation of lithium zirconate were solved, and the high purity and texture uniformity of lithium zirconate were achieved, and the mass production process was simplified.

CN119461474APending Publication Date: 2025-02-18XIAN JI-LI ELECTRONIC & CHEM ENG CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411598985.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Among the existing lithium zirconate preparation methods, the solid-phase sintering method has a high synthesis temperature, high energy consumption, and impure phases of the preparation, resulting in difficulty in mass production.

Method used

Lithium zirconate is prepared by zirconia purification and wet mixing methods. The impurities are eluteed by hydrochloric acid and mixed with wet and crushing to ensure uniform distribution and high purity of lithium and zirconium.

Benefits of technology

The texture uniformity and high purity of lithium zirconate (more than 99.9%) are achieved, the synthesis temperature and energy consumption are reduced, and the mass production process is simplified.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461474A_ABST
    Figure CN119461474A_ABST
Patent Text Reader

Abstract

In order to solve the technical problems that lithium zirconate prepared by an existing preparation method of lithium zirconate is non-uniform in texture and relatively low in purity, the invention provides a preparation method of battery-grade lithium zirconate, and lithium zirconate with uniform texture and the purity of 99.9% or above can be produced. Impurities capable of being dissolved in hydrochloric acid in zirconium oxide are washed away through hydrochloric acid, and the purity of raw materials for preparing lithium zirconate is guaranteed; according to the preparation method, the distribution uniformity of lithium and zirconium in the prepared lithium zirconate is ensured by adopting wet mixing and crushing, grinding and mixing, and meanwhile, lithium acetate and zirconium oxide can fully react when lithium acetate and zirconium oxide which are secondarily mixed are subsequently heated and dried, so that the purity of the lithium zirconate is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing lithium zirconate. Background Art

[0002] Lithium-ion batteries made of lithium zirconate have high energy density, long cycle life and safety in use. Among them, the high energy density makes it particularly suitable for energy storage systems, which can improve energy utilization efficiency and the reliability of renewable energy; the long cycle life and safety in use make it suitable for mobile power supplies, smart wearable devices and other fields.

[0003] At present, there are many methods for synthesizing lithium zirconate, and the commonly used synthesis methods include solid-phase sintering method, precipitation method and sol-gel method; among them, the solid-phase sintering method has a simple preparation process and is easy to realize industrial mass production, but the current solid-phase sintering preparation of lithium zirconate has a high synthesis temperature, high energy consumption, impure prepared phase, and difficulty in mass production; the reaction rate and conditions in the precipitation method are difficult to control, and it is not easy to obtain pure and uniform lithium zirconate particles; and the gel used in the sol-gel method is expensive, and it is not easy to realize its mass industrial production.

[0004] In order to overcome the technical problems of high synthesis temperature and impure phase of the solid phase sintering method, a lithium zirconate material and its preparation method are disclosed in the Chinese patent document with application number 202310126773.3. The lithium source material (one or more of lithium carbonate, lithium hydroxide, lithium nitrate, and lithium acetate) and the zirconium source material (one or more of zirconium oxide, zirconium nitrate, and zirconium hydroxide) with a particle size Dv50 of 0.5-3 microns are placed in a high-speed mixer, and then the sintering agent fluoride is added to mix evenly at high speed. After crystallization and crushing, a pure phase lithium zirconate material is finally obtained. Due to the use of sintering agent fluoride, the synthesis temperature of lithium zirconate material prepared by the solid phase method is reduced; since the relative atomic mass of zirconium is heavier than that of lithium, the use of zirconium source material with a smaller particle size can improve the projection activity, which is conducive to the combination of lithium and zirconium to form lithium zirconate and shortens the synthesis time. However, since this method involves solid-phase mixing, the uniformity of the mixing of lithium and zirconium cannot be guaranteed and the required mixing time is very long, resulting in low efficiency. In addition, since this method involves the addition of fluoride as a flux, impurities are inevitably introduced, resulting in a low purity of the prepared lithium zirconate. Summary of the invention

[0005] In order to solve the technical problem that lithium zirconate prepared by the existing lithium zirconate preparation method has uneven texture and low purity, the present invention provides a battery-grade lithium zirconate preparation method, which can produce lithium zirconate with uniform texture and purity of more than 99.9%.

[0006] The technical solution of the present invention is:

[0007] A method for preparing battery-grade lithium zirconate, which is special in that it comprises the following steps:

[0008] Step 1, purifying zirconium oxide;

[0009] Step 1.1 Grind industrial-grade zirconium oxide to a particle size distribution D97 of 15-25 μm to obtain ultrafine zirconium oxide powder;

[0010] Step 1.2: Take analytical pure hydrochloric acid and add pure water to dilute it by 1 time, then add the ultrafine zirconium oxide powder thereto, the mass ratio of the ultrafine zirconium oxide powder to the diluted hydrochloric acid is 1:4, and obtain a suspension of hydrochloric acid and zirconium oxide;

[0011] Step 1.3: The suspension is heated, boiled and washed, settled, the precipitate is collected, centrifuged and washed with water until the chlorine content is less than 50 ppm and the contents of Fe, Co, Ni, Cu, Ti, V, Cr and Cd are all less than 1 ppm, to obtain a battery-grade zirconium oxide filter cake;

[0012] Step 1.4: drying the battery-grade zirconium oxide filter cake to obtain battery-grade zirconium oxide;

[0013] Step 2, preparing lithium acetate;

[0014] Step 2.1 Take analytical pure acetic acid, add water to dilute it to a mass fraction of less than or equal to 20%, add battery-grade lithium carbonate thereto, the molar ratio of acetic acid to lithium carbonate is greater than or equal to 3:1, dissolve it until it is colorless and transparent, and obtain a crude lithium acetate solution; the analytical pure acetic acid is diluted to a mass fraction of less than or equal to 20% here because it is considered that too high a mass fraction will make the reaction solution too viscous, and the carbon dioxide cannot be quickly released during the generation process, resulting in the volume expansion of the reaction solution, and there is a risk of the reaction solution bubbling out; if the mass fraction of acetic acid is low, it will only affect the time of subsequent concentration and crystallization, and more water can be evaporated during the concentration and crystallization; there are three reasons for the excess acetic acid here: one is to fully dissolve the lithium carbonate, the second is to take into account that the acetic acid will volatilize during the dissolution process, and the third is to facilitate the concentration and crystallization of the subsequent steps; the reaction equation involved in this step: Li2CO3+2CH3COOH====2CH3COOLi+H2O+CO2;

[0015] Step 2.2: filtering the crude lithium acetate solution to remove insoluble matter and mechanical impurities to obtain a refined lithium acetate solution;

[0016] Step 2.3: The lithium acetate solution is heated to concentrate and crystallize. After a large amount of crystals appear, the crystals are cooled and then centrifuged. The contents of Fe, Co, Ni, Cu, Ti, V, Cr, and Cd in the controlled crystals are all less than 1 ppm, so as to obtain battery-grade lithium acetate crystals.

[0017] Step 3, preparing lithium zirconate;

[0018] Step 3.1 Take the battery-grade lithium acetate crystals and the battery-grade zirconium oxide, add ultrapure water, and stir them evenly until they are non-flowing and wet, to obtain a mixed mud of lithium acetate and zirconium oxide; the molar ratio of lithium acetate to zirconium oxide is 2:1, and the mass of ultrapure water is 1 / 2.1-1 / 1.8 of the total mass of lithium acetate and zirconium oxide. If there is too much water, the concentration will be too low to form a muddy state, and if there is too little water, the state formed will be difficult to mix, and the effect of wet mixing uniformity cannot be achieved;

[0019] Step 3.2: evaporate the mixed mud to dryness (when the temperature rises to above 150° C., lithium acetate will undergo vitrification and fully wrap the zirconium oxide, so that the subsequent steps can fully react), to obtain a glassy mixture of lithium acetate and zirconium oxide;

[0020] Step 3.3: crushing the lithium acetate and zirconium oxide glassy mixture to a D0.97 of 20-30 microns to obtain a secondary mixed lithium acetate and zirconium oxide mixture;

[0021] Step 3.4: Heat and dry the secondary mixed lithium acetate and zirconium oxide mixture obtained in step 3.3 to obtain a battery-grade lithium zirconate block. The reaction equation involved in this step is: 2CH3COOLi+ZrO2+4O2====Li2ZrO3+4CO2+3H2O;

[0022] Step 3.5: The battery-grade lithium zirconate block is crushed and sieved to obtain a battery-grade lithium zirconate product. A sample is taken from the obtained battery-grade lithium zirconate product for testing: the sample is qualitatively identified as lithium zirconate using an Xrd diffractometer; the sample is tested using an Agilent-5110-ICP-OES, and the contents of Fe, Co, Ni, Cu, Ti, V, Cr, and Cd in the sample are all less than 2ppm, the Cl ion content in chemical analysis is less than 50ppm, and the purity is greater than 99.9%.

[0023] Furthermore, in step 1.3, the suspension is heated, stirred, boiled and washed for 3-4 hours at 80-90° C. and 60-80 rpm, and then settled for 2-3 hours.

[0024] Furthermore, in step 1.4, the battery-grade zirconium oxide filter cake is dried at a temperature of 300-500° C. for 2-3 hours to obtain battery-grade zirconium oxide.

[0025] Furthermore, in step 2.3, the lithium acetate solution is heated to 110-120°C for concentrated crystallization. After a large amount of crystals appear, the solution is cooled and crystallized to 30-40°C. The crystals are then wrapped with filter cloth (the mesh size of the filter cloth is sufficient as long as the crystal particles do not leak out) and centrifuged at a speed of 800-1000 rpm (too low a centrifugal speed will result in excessive water retention). The contents of Fe, Co, Ni, Cu, Ti, V, Cr, and Cd in the controlled crystals are all less than 1 ppm to obtain battery-grade lithium acetate crystals.

[0026] Furthermore, the evaporation operation in step 3.2 refers to drying the mixed mud at 200-250° C. for 3-4 hours.

[0027] Furthermore, step 3.4 is to dry the secondary mixed lithium acetate and zirconium oxide mixture at 900-1000°C (temperature below the lower limit of the range cannot form dense crystalline lithium zirconate, and temperature above the upper limit of the range will result in waste of electrical energy) for 3-4 hours to obtain battery-grade lithium zirconate blocks.

[0028] The advantages of the present invention are:

[0029] 1. The present invention utilizes the extremely stable properties of zirconium oxide, uses hydrochloric acid to wash away impurities in zirconium oxide that are soluble in hydrochloric acid, purifies zirconium oxide, and ensures the purity of raw materials for preparing lithium zirconate;

[0030] 2. If lithium and zirconium are not mixed evenly, the content of unreacted lithium and zirconium will increase, resulting in insufficient purity of the final lithium zirconate. In order to overcome this shortcoming, the present invention adopts wet mixing + crushing and grinding mixing to ensure the uniformity of the distribution of lithium and zirconium in the prepared lithium zirconate: first, wet mixing is adopted to mix lithium acetate and zirconium oxide to obtain a mixed mud of lithium acetate and zirconium oxide, and the mixing time is short and the mixing is more uniform; then, when the lithium acetate is heated to above 150°C, a vitrification phenomenon will occur, and the mixed mud of lithium acetate and zirconium oxide is heated and evaporated to dryness, so that the lithium acetate can fully wrap the zirconium oxide after vitrification, and then the glassy mixture of lithium acetate and zirconium oxide is crushed to obtain a secondary mixed mixture of lithium acetate and zirconium oxide.

[0031] 3. The present invention not only ensures the uniform distribution of lithium and zirconium in lithium zirconate through wet mixing + crushing and grinding mixing, but also enables lithium acetate and zirconium oxide to fully react when the secondary mixed lithium acetate and zirconium oxide are subsequently heated and dried, thereby ensuring the purity of lithium zirconate, which can reach more than 99.9%.

[0032] 4. The present invention does not add fluoride sintering aids during the preparation process, thereby reducing the introduction of impurities and ensuring the purity of the product. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is the XRD diagram of the lithium zirconate prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0034] The present invention is further described in detail below by way of examples.

[0035] Example 1

[0036] In this embodiment, lithium zirconate is prepared by the following steps:

[0037] Step 1, purifying zirconium oxide;

[0038] Step 1.1 Take industrial-grade zirconium oxide and add it into a zirconium ball grinder for grinding until the particle size distribution D97 is 15 μm to obtain ultrafine zirconium oxide powder;

[0039] Step 1.2: Take analytical pure hydrochloric acid, add pure water to dilute it, the mass ratio of hydrochloric acid to pure water is 1:1, and then add the ultrafine zirconium oxide powder obtained in step 1.1 to the diluted hydrochloric acid, the mass ratio of zirconium oxide to the diluted hydrochloric acid is 1:4, to obtain a suspension of hydrochloric acid and zirconium oxide;

[0040] Step 1.3: Add the suspension obtained in step 1.2 to an enameled reactor, heat it to 90°C and keep it warm, stir and boil it at a speed of 80 rpm for 3 hours, put it in a PP barrel, settle it for 3 hours, remove the supernatant, centrifuge the precipitate, wash it with water, wash it with water until the chlorine content is less than 50ppm, and remove other metal ions soluble in hydrochloric acid, take a sample and send it to the laboratory for testing, when the content of impurities Fe, Co, Ni, Cu, Ti, V, Cr, and Cd in the precipitate is less than 1ppm, a battery-grade zirconium oxide filter cake is obtained;

[0041] Step 1.4: Dry the zirconium oxide filter cake obtained in step 1.3 at a drying temperature of 300° C. for 3 hours to obtain battery-grade zirconium oxide.

[0042] Step 2, preparing lithium acetate;

[0043] Step 2.1 Take analytical pure acetic acid and dilute it with water to a mass fraction of 20%, add battery grade lithium carbonate thereto, the molar ratio of acetic acid to lithium carbonate is 3:1, dissolve until colorless and transparent, and obtain a crude lithium acetate solution;

[0044] Step 2.2: Filter the crude lithium acetate solution obtained in step 2.1 through a filter with a filtration accuracy of 0.5 microns to remove insoluble matter and mechanical impurities to obtain a refined lithium acetate solution;

[0045] Step 2.3: Add the fine lithium acetate solution into an enameled reactor and heat to 110°C for concentration and crystallization. After a large amount of crystals are concentrated, place them in a PP plastic barrel and continue to cool and crystallize. After cooling to 30°C, wrap the crystals with 800-mesh filter cloth and centrifuge at 800 rpm. After controlling Fe, Co, Ni, Cu, Ti, V, Cr, Cd, etc. to less than 1ppm, battery-grade lithium acetate crystals are obtained.

[0046] Step 3, preparing lithium zirconate;

[0047] Step 3.1 Take the battery-grade lithium acetate crystals obtained in step 2.3 and add them to a polytetrafluoroethylene plastic barrel, then add the battery-grade zirconium oxide obtained in step 1.4 to the polytetrafluoroethylene barrel, the molar ratio of lithium acetate to zirconium oxide is 2:1, then add ultrapure water, perform mud-mixing operation, stir well to achieve a non-flowing and wet state, the mass of the added water is 1 / 2 of the total mass of lithium acetate and zirconium oxide, and obtain a mixed mud of lithium acetate and zirconium oxide;

[0048] Step 3.2: adding the mixed mud of lithium acetate and zirconium oxide obtained in step 3.1 into a tetrafluoroethylene crucible for evaporation and drying, specifically, drying at 200° C. for 4 hours to obtain a glassy mixture of lithium acetate and zirconium oxide;

[0049] Step 3.3: Add the lithium acetate and zirconium oxide glassy mixture obtained in step 3.2 into a zirconium ball mill for ball milling and mixing, and grind to a D97 of 20 microns to obtain a secondary mixed lithium acetate and zirconium oxide mixture;

[0050] Step 3.4: putting the secondary mixed lithium acetate and zirconium oxide mixture obtained in step 3.3 into a graphite crucible, compacting it manually, and drying it at 1000° C. for 3 hours to obtain a battery-grade lithium zirconate block;

[0051] Step 3.5: Remove the adhered graphite from the battery-grade lithium zirconate block obtained in step 3.4, then crush it and pass it through an 80-mesh sieve to obtain a battery-grade lithium zirconate product. The battery-grade lithium zirconate product obtained in step 3.5 is sampled for testing: an XRD diffractometer is used to identify the sample as lithium zirconate, and the XRD pattern is as follows: Figure 1 As shown; using Agilent-5110-ICP-OES detection, the contents of Fe, Co, Ni, Cu, Ti, V, Cr, and Cd in the sample are all less than 2ppm, the chemical analysis Cl ion is less than 50ppm, and the purity is greater than 99.9%.

[0052] Example 2

[0053] In this embodiment, lithium zirconate is prepared by the following steps:

[0054] Step 1, purifying zirconium oxide;

[0055] Step 1.1 Take industrial-grade zirconium oxide and add it into a zirconium ball grinder for grinding until the particle size distribution D97 is 18 μm to obtain ultrafine zirconium oxide powder;

[0056] Step 1.2: Take analytical pure hydrochloric acid, add pure water to dilute it, the mass ratio of hydrochloric acid to pure water is 1:1, and then add the ultrafine zirconium oxide powder obtained in step 1.1 to the diluted hydrochloric acid, the mass ratio of zirconium oxide to the diluted hydrochloric acid is 1:4, to obtain a suspension of hydrochloric acid and zirconium oxide;

[0057] Step 1.3: Add the suspension obtained in step 1.2 to an enameled reactor, heat it to 85°C and keep it warm, stir and boil it at a speed of 70 rpm for 3.5 hours, put it in a PP barrel, settle it for 2.5 hours, remove the supernatant, centrifuge the precipitate, wash it with water, wash it with water until the chlorine content is less than 50ppm, and remove other metal ions soluble in hydrochloric acid, take a sample and send it to the laboratory for testing, when the content of impurities Fe, Co, Ni, Cu, Ti, V, Cr, and Cd in the precipitate is less than 1ppm, a battery-grade zirconium oxide filter cake is obtained;

[0058] Step 1.4: Dry the zirconium oxide filter cake obtained in step 1.3 at a drying temperature of 400° C. for 3.5 hours to obtain battery-grade zirconium oxide.

[0059] Step 2, preparing lithium acetate;

[0060] Step 2.1 Take analytical pure acetic acid and dilute it with water to a mass fraction of 18%, add battery grade lithium carbonate thereto, the molar ratio of acetic acid to lithium carbonate is 3.5:1, dissolve until colorless and transparent, and obtain a crude lithium acetate solution;

[0061] Step 2.2: Filter the crude lithium acetate solution obtained in step 2.1 through a filter with a filtration accuracy of 0.5 microns to remove insoluble matter and mechanical impurities to obtain a refined lithium acetate solution;

[0062] Step 2.3: Add the fine lithium acetate solution into an enameled reactor and heat to 115°C for concentration and crystallization. After a large amount of crystals are concentrated, place them in a PP plastic barrel and continue to cool and crystallize. After cooling to 35°C, wrap the crystals with a 900-mesh filter cloth and centrifuge at 900 rpm. After controlling Fe, Co, Ni, Cu, Ti, V, Cr, Cd, etc. to less than 1ppm, battery-grade lithium acetate crystals are obtained.

[0063] Step 3, preparing lithium zirconate;

[0064] Step 3.1 Take the battery-grade lithium acetate crystals obtained in step 2.3 and add them to a polytetrafluoroethylene plastic barrel, then add the battery-grade zirconium oxide obtained in step 1.4 to the polytetrafluoroethylene barrel, the molar ratio of lithium acetate to zirconium oxide is 2:1, then add ultrapure water, perform mud-mixing operation, stir well to achieve a non-flowing and wet state, the mass of the added water is 1 / 2.1 of the total mass of lithium acetate and zirconium oxide, and obtain a mixed mud of lithium acetate and zirconium oxide;

[0065] Step 3.2: adding the mixed mud of lithium acetate and zirconium oxide obtained in step 3.1 into a tetrafluoroethylene crucible for evaporation and drying, specifically, drying at 250° C. for 3 hours to obtain a glassy mixture of lithium acetate and zirconium oxide;

[0066] Step 3.3: Add the lithium acetate and zirconium oxide glassy mixture obtained in step 3.2 into a zirconium ball mill for ball milling and mixing, and grind to a D97 of 25 microns to obtain a secondary mixed lithium acetate and zirconium oxide mixture;

[0067] Step 3.4: putting the secondary mixed lithium acetate and zirconium oxide mixture obtained in step 3.3 into a graphite crucible, manually compacting it, and drying it at 900° C. for 4 hours to obtain a battery-grade lithium zirconate block;

[0068] Step 3.5: Remove the adhered graphite from the battery-grade lithium zirconate block obtained in step 3.4, then crush it and pass it through a 90-mesh sieve to obtain a battery-grade lithium zirconate product. The battery-grade lithium zirconate product obtained in step 3.5 is sampled for testing: an XRD diffractometer is used to identify the sample as lithium zirconate, and the XRD pattern is as follows: Figure 1 As shown; using Agilent-5110-ICP-OES detection, the contents of Fe, Co, Ni, Cu, Ti, V, Cr, and Cd in the sample are all less than 2ppm, the chemical analysis Cl ion is less than 50ppm, and the purity is greater than 99.9%.

[0069] Example 3

[0070] In this embodiment, lithium zirconate is prepared by the following steps:

[0071] Step 1, purifying zirconium oxide;

[0072] Step 1.1 Take industrial-grade zirconium oxide and add it into a zirconium ball grinder for grinding until the particle size distribution D97 is 25 μm to obtain ultrafine zirconium oxide powder;

[0073] Step 1.2: Take analytical pure hydrochloric acid, add pure water to dilute it, the mass ratio of hydrochloric acid to pure water is 1:1, and then add the ultrafine zirconium oxide powder obtained in step 1.1 to the diluted hydrochloric acid, the mass ratio of zirconium oxide to the diluted hydrochloric acid is 1:4, to obtain a suspension of hydrochloric acid and zirconium oxide;

[0074] Step 1.3: Add the suspension obtained in step 1.2 to an enameled reactor, heat it to 80°C and keep it warm, stir and boil it at a speed of 60 rpm for 4 hours, put it in a PP barrel, settle it for 2 hours, remove the supernatant, centrifuge the precipitate, wash it with water, wash it with water until the chlorine content is less than 50ppm, and remove other metal ions soluble in hydrochloric acid, take a sample and send it to the laboratory for testing, when the content of impurities Fe, Co, Ni, Cu, Ti, V, Cr, and Cd in the precipitate is less than 1ppm, a battery-grade zirconium oxide filter cake is obtained;

[0075] Step 1.4: Dry the zirconium oxide filter cake obtained in step 1.3 at a drying temperature of 500° C. for 2 hours to obtain battery-grade zirconium oxide.

[0076] Step 2, preparing lithium acetate;

[0077] Step 2.1 Take analytical pure acetic acid and dilute it with water to a mass fraction of 15%, add battery grade lithium carbonate thereto, the molar ratio of acetic acid to lithium carbonate is 4:1, dissolve until colorless and transparent, and obtain a crude lithium acetate solution;

[0078] Step 2.2: Filter the crude lithium acetate solution obtained in step 2.1 through a filter with a filtration accuracy of 0.5 microns to remove insoluble matter and mechanical impurities to obtain a refined lithium acetate solution;

[0079] Step 2.3: Add the fine lithium acetate solution into an enameled reactor and heat to 120°C for concentration and crystallization. After a large amount of crystals are concentrated, place them in a PP plastic barrel and continue to cool and crystallize. After cooling to 40°C, wrap the crystals with 850-mesh filter cloth and centrifuge at 1000 rpm. After controlling Fe, Co, Ni, Cu, Ti, V, Cr, Cd, etc. to less than 1 ppm, battery-grade lithium acetate crystals are obtained.

[0080] Step 3, preparing lithium zirconate;

[0081] Step 3.1 Take the battery-grade lithium acetate crystals obtained in step 2.3 and add them to a polytetrafluoro plastic barrel, then add the battery-grade zirconium oxide obtained in step 1.4 to the polytetrafluoro barrel, the molar ratio of lithium acetate to zirconium oxide is 2:1, then add ultrapure water, perform mud operation, stir well to achieve a non-flowing and wet state, the mass of water added is 1 / 1.8 of the total mass of lithium acetate and zirconium oxide, and obtain a mixed mud of lithium acetate and zirconium oxide;

[0082] Step 3.2: adding the mixed mud of lithium acetate and zirconium oxide obtained in step 3.1 into a tetrafluoroethylene crucible for evaporation and drying, specifically, drying at 220° C. for 3.5 hours to obtain a glassy mixture of lithium acetate and zirconium oxide;

[0083] Step 3.3: Add the lithium acetate and zirconium oxide glassy mixture obtained in step 3.2 into a zirconium ball mill for ball milling and mixing, and grind to a D97 of 30 microns to obtain a secondary mixed lithium acetate and zirconium oxide mixture;

[0084] Step 3.4: putting the secondary mixed lithium acetate and zirconium oxide mixture obtained in step 3.3 into a graphite crucible, compacting it manually, and drying it at 950° C. for 3.5 hours to obtain a battery-grade lithium zirconate block;

[0085] Step 3.5: Remove the adhered graphite from the battery-grade lithium zirconate block obtained in step 3.4, then crush it and pass it through an 85-mesh sieve to obtain a battery-grade lithium zirconate product. The battery-grade lithium zirconate product obtained in step 3.5 is sampled for testing: an XRD diffractometer is used to identify the sample as lithium zirconate, and the XRD pattern is as follows: Figure 1 As shown; using Agilent-5110-ICP-OES detection, the contents of Fe, Co, Ni, Cu, Ti, V, Cr, and Cd in the sample are all less than 2ppm, the chemical analysis Cl ion is less than 50ppm, and the purity is greater than 99.9%.

Claims

1. A method for preparing battery-grade lithium zirconate, characterized in that: The following steps are involved: Step 1, purifying zirconium oxide; Step 1.1 Grind industrial-grade zirconium oxide to a particle size distribution D0.97 of 15-25 μm to obtain ultrafine zirconium oxide powder; Step 1.2: Take analytical pure hydrochloric acid and add pure water to dilute it by 1 time, then add the ultrafine zirconium oxide powder thereto, the mass ratio of the ultrafine zirconium oxide powder to the diluted hydrochloric acid is 1:4, and obtain a suspension of hydrochloric acid and zirconium oxide; Step 1.3: The suspension is heated, boiled and washed, settled, the precipitate is collected, centrifuged and washed with water until the chlorine content is less than 50 ppm and the contents of Fe, Co, Ni, Cu, Ti, V, Cr and Cd are all less than 1 ppm, to obtain a battery-grade zirconium oxide filter cake; Step 1.4: drying the battery-grade zirconium oxide filter cake to obtain battery-grade zirconium oxide; Step 2, preparing lithium acetate; Step 2.1 Take analytical pure acetic acid, add water to dilute it to a mass fraction of less than or equal to 20%, add battery-grade lithium carbonate thereto, the molar ratio of acetic acid to lithium carbonate is greater than or equal to 3:1, dissolve it until it is colorless and transparent, and obtain a crude lithium acetate solution; Step 2.2: filtering the crude lithium acetate solution to remove insoluble matter and mechanical impurities to obtain a refined lithium acetate solution; Step 2.3: The lithium acetate solution is heated to concentrate and crystallize, and after a large amount of crystals appear, the solution is cooled and crystallized, and then centrifuged. The contents of Fe, Co, Ni, Cu, Ti, V, Cr, and Cd in the controlled crystals are all less than 1 ppm, so as to obtain battery-grade lithium acetate crystals; Step 3, preparing lithium zirconate; Step 3.1 Take the battery-grade lithium acetate crystals and the battery-grade zirconium oxide, add ultrapure water, and stir them evenly until they are not flowing and wet, to obtain a mixed mud of lithium acetate and zirconium oxide; the molar ratio of lithium acetate to zirconium oxide is 2:1, and the mass of ultrapure water is 1 / 2 of the total mass of lithium acetate and zirconium oxide; Step 3.2: evaporating the mixed mud to dryness to obtain a glassy mixture of lithium acetate and zirconium oxide; Step 3.3: crushing the lithium acetate and zirconium oxide glassy mixture to a D0.97 of 20-30 microns to obtain a secondary mixed lithium acetate and zirconium oxide mixture; Step 3.4: heating and drying the secondary mixed lithium acetate and zirconium oxide mixture to obtain a battery-grade lithium zirconate block; Step 3.5: crushing the battery-grade lithium zirconate block material, sieving, and obtaining a battery-grade lithium zirconate finished product.

2. The method for preparing battery-grade lithium zirconate according to claim 1, characterized in that: In step 1.3, the suspension is heated, stirred and boiled at 80-90° C. and 60-80 rpm for 3-4 hours, and then allowed to settle for 2-3 hours.

3. The method for preparing battery-grade lithium zirconate according to claim 2, characterized in that: In step 1.4, the battery-grade zirconium oxide filter cake is dried at a temperature of 300-500° C. for 2-3 hours to obtain battery-grade zirconium oxide.

4. The method for preparing battery-grade lithium zirconate according to claim 3, characterized in that: In step 2.3, the lithium acetate solution is heated to 110-120° C. for concentrated crystallization. After a large amount of crystals appear, the solution is cooled and crystallized to 30-40° C., and then the crystals are wrapped with 800-mesh filter cloth and centrifuged at a speed of 800-1000 rpm. The contents of Fe, Co, Ni, Cu, Ti, V, Cr, and Cd in the controlled crystals are all less than 1 ppm, and battery-grade lithium acetate crystals are obtained.

5. The method for preparing battery-grade lithium zirconate according to claim 4, characterized in that: The evaporation operation in step 3.2 refers to drying the mixed mud at 200-250°C for 3-4 hours.

6. The method for preparing battery-grade lithium zirconate according to claim 5, characterized in that: Step 3.4 is to dry the secondary mixed lithium acetate and zirconium oxide mixture at 900-1000° C. for 3-4 hours to obtain battery-grade lithium zirconate blocks.

7. A battery-grade lithium zirconate, characterized in that: The battery-grade lithium zirconate is prepared by the method described in any one of claims 1-6.

Citation Information

Patent Citations

  • A lithium zirconate material and its preparation method and application

    CN116119711B